Catalyst for treating tail gas of gas-fueled vehicle and preparation method of catalyst

By using precious metal Pd in ​​natural gas automobile catalysts to support the mixed support of cerium-zirconium aluminum and cerium-zirconium composite materials, and using a one-step reduction pulping method, the problems of complex preparation processes and large energy consumption in the prior art are solved, and efficient and low-cost catalyst preparation and excellent catalytic performance are achieved.

CN119524843AActive Publication Date: 2025-02-28SINOCAT ENVIRONMENTAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411830016.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the prior art, the preparation process of natural gas automobile catalysts is complex, requiring multiple layers of coating, drying and roasting, resulting in high costs and large energy consumption.

Method used

The preparation process is simplified by reducing one-step pulping method using a catalyst supported by noble metal Pd on a mixed support of cerium-zirconium aluminum composite material and cerium-zirconium composite material.

Benefits of technology

It improves the catalytic performance of natural gas catalysts, reduces energy consumption, simplifies the preparation process, reduces costs, and significantly improves the anti-aging performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524843A_ABST
    Figure CN119524843A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for treating gas-fueled vehicle exhaust and a preparation method thereof.The catalyst is characterized in that precious metal Pd is loaded on a mixed carrier of two composite materials, the composite materials are composed of a material 1 and a material 2, the material 1 is a cerium-zirconium-aluminum composite material, and the cerium-zirconium-aluminum composite material comprises 0-20% of Ce, 0-10% of Zr, 68-98% of Al and 2% of other rare earth metal; and the material 2 is a cerium-zirconium composite material, and the cerium-zirconium composite material comprises 10-45% of Ce, 35-45% of Zr and 0-20% of other rare earth metals. The preparation method is simple, the preparation process is easy to operate, and the catalyst has excellent CH4 conversion performance, low energy consumption and excellent aging resistance. The catalyst is prepared by adopting a reduction one-step pulping method, so that the catalytic performance of the natural gas catalyst is improved, the energy consumption in the process of preparing the catalyst by adopting a traditional impregnation method is reduced, and more energy is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile exhaust catalysis, and in particular to a catalyst for treating natural gas automobile exhaust and a preparation method thereof. Background Art

[0002] With the development of the times, energy and environmental issues have gradually become the focus of people's attention. The gradual depletion of oil resources and a series of environmental problems caused by oil combustion have made people focus on the development of alternative oil. So far, natural gas has gradually become one of the best alternative energy sources. As a clean energy, natural gas has the advantages of abundant reserves, high combustion efficiency and low emissions. Compared with traditional gasoline vehicles, the CO, HC and NO in the exhaust gas of natural gas vehicles are x The emission of pollutants such as carbon monoxide is lower and it is environmentally friendly. Therefore, developing efficient and stable natural gas vehicle catalysts to reduce methane emissions has become an important direction for the current development of natural gas vehicles.

[0003] Traditional natural gas three-effect catalysts are generally Pt, Pd, Rh active components doped with transition metals or alkali metals as additives, oxygen storage materials or alumina material carrier catalysts, and the active components and additives are loaded on the catalytic carrier by high-temperature drying and roasting by impregnation method, and then coated on the honeycomb ceramic carrier through multiple layers. More and more engine manufacturers are demanding to reduce costs continuously, so reducing the catalyst preparation process has become one of the means to reduce the production cost of catalysts.

[0004] Chinese patent CN114870860 A discloses a perovskite catalyst, which uses different reducing agents as dispersants to adjust the pH of the solution and forms sols with different transition metal salts and alumina, and then sintering to obtain different catalyst powders. The layered coating method is used to make different coatings play different roles, and the matching use reduces the emission of pollutants. x A y Mn z B 1-z As the first coating, modified alumina is used as the second coating, and Pt, Rh or Pd, Rh precious metals are loaded into cerium-zirconium solid solution as the third coating. Each layer is coated and dried separately, and when all the coatings are dried, they are calcined. Multiple coatings and drying increase the production cost of the catalyst.

[0005] Chinese patent CN115970687A discloses a method for preparing a Pt-based catalyst, in which the noble metal is loaded on cerium zirconium oxide in a hydrophobic solution to improve the dispersion of the noble metal active component and thus improve the catalytic activity. After a reducing agent is added during the preparation of the inner layer powder of the catalyst, the valence state of the noble metal Pt and Pd is reduced to form an atomic-level bond, which inhibits the migration and agglomeration of the noble metal and improves the anti-aging performance of the catalyst.

[0006] The above technical solutions all require multi-layer coating, drying and calcination, and the preparation process parameters are relatively complex, so it is necessary to develop catalysts with simpler preparation processes, lower precious metal content and higher catalytic efficiency. Summary of the invention

[0007] The purpose of the present invention is to provide a catalyst for treating natural gas automobile exhaust and a preparation method thereof, so as to solve the technical problems in the prior art that multi-layer coating, drying and calcination are required and the preparation process is complicated.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The present invention provides a catalyst for treating natural gas automobile exhaust. The catalyst is a catalyst in which precious metal Pd is loaded on a mixed carrier of two composite materials. The composite material consists of material 1 and material 2. Material 1 is a cerium-zirconium-aluminum composite material, wherein the content ratio of cerium-zirconium-aluminum is 0-20% Ce, 0-10% Zr, 68-98% Al, and the content of other rare earth metal La is 2%; material 2 is a cerium-zirconium composite material, wherein the ratio of cerium-zirconium is 10-45% Ce, 35-45% Zr, and the content of other rare earth metal La is 0-20%.

[0010] Furthermore, the mass ratio of Pd in ​​material 1 and material 2 is 1:1.

[0011] Furthermore, the mass ratio of the material 1 to the material 2 is 1:10 to 10:1.

[0012] The present invention also provides a method for preparing a catalyst for treating natural gas automobile exhaust, comprising the following steps:

[0013] Step 1: Preparation of slurry

[0014] (1) taking palladium nitrate solution, material 1, material 2, a reducing agent and deionized water in proportion, mixing them, and immersing them in a water bath at 60° C. and stirring;

[0015] (2) adding the slurry prepared in step (1) into a ball mill and adding acetic acid to adjust the pH of the slurry to 2-7, adding a binder to keep the slurry viscous, and placing it into a ball mill and stirring rapidly;

[0016] Step 2: Sizing and Drying

[0017] The slurry prepared in (2) was coated on a cordierite ceramic carrier, dried for 2-4 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0018] Furthermore, the reducing agent is one of ascorbic acid, glucose and ethylene glycol.

[0019] Furthermore, the content of the reducing agent is 5 times the amount of the precious metal Pd substance.

[0020] Furthermore, the present invention uses cordierite honeycomb ceramics as a carrier, cerium-zirconium-aluminum material as a coating, and precious metal Pd as a catalyst active component, and the coating coating amount is 120 g / L.

[0021] In the preparation process of the catalyst, the honeycomb ceramic carrier used is a cube with a honeycomb-like structure. There are many grid-like channels in the cube. The thin channel wall can greatly increase the surface area of ​​the carrier. The catalyst slurry is coated in this channel. The coating amount of the catalyst can be determined by the volume of the cube and the mass of the slurry coated on the cube. Therefore, it can be expressed in g / L.

[0022] Further, step 1: preparation of slurry

[0023] (1) Take a palladium nitrate solution, one part of material 1, two parts of material 2, a reducing agent and 80 ml of deionized water in proportion, mix them, and immerse them in a water bath at 60° C. and stir;

[0024] (2) adding the slurry prepared in step (1) into a ball mill and adding acetic acid to adjust the pH of the slurry to 2-7, adding a binder to keep the slurry viscous, and placing it into a ball mill and stirring rapidly;

[0025] Step 2: Sizing and Drying

[0026] The slurry prepared in (2) was coated on a cordierite ceramic carrier, dried for 2-4 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0027] Further, step 1: preparation of slurry

[0028] (1) Take palladium nitrate solution, two parts of material 1, one part of material 2, a reducing agent and 80 ml of deionized water in proportion, mix them, and immerse them in a water bath at 60° C. and stir;

[0029] (2) adding the slurry prepared in step (1) into a ball mill and adding acetic acid to adjust the pH of the slurry to 2-7, adding a binder to keep the slurry viscous, and placing it into a ball mill and stirring rapidly;

[0030] Step 2: Sizing and Drying

[0031] The slurry prepared in (2) was coated on a cordierite ceramic carrier, dried for 2-4 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0032] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects:

[0033] (1) The present invention adopts a one-step reduction pulping method to prepare the catalyst, which improves the catalytic performance of the natural gas catalyst and reduces the energy consumption in the traditional impregnation method to prepare the catalyst, thereby being more energy-efficient.

[0034] (2) The present invention provides a catalyst for treating natural gas automobile exhaust and a preparation method thereof. The preparation method is simple and the preparation process is easy to operate. The catalyst has excellent CH 4 High conversion performance, low energy consumption and excellent anti-aging performance.

[0035] (3) The catalytic performance of methane prepared by the catalyst using the reducing agent of the present invention is significantly improved, wherein the catalyst prepared by one-step pulping with the addition of the reducing agent ascorbic acid, glucose, and ethylene glycol is T 50 The ignition temperature is significantly lower than that of the aged catalyst. 50 The temperature is also maintained at around 350°C, and the catalytic effect is better than that of traditional catalysts. At the same time, the direct sample preparation and roasting of the reduced slurry in the slurry preparation process reduces the steps of first drying and roasting the powder and then preparing the slurry in the traditional catalyst preparation process, thus reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0037] Figure 1 These are the test results for evaluating the activity of fresh catalysts of Comparative Examples 1-3 of the present invention;

[0038] Figure 2 These are the results of the activity evaluation tests of the aged catalysts of Comparative Examples 1-3 of the present invention;

[0039] Figure 3 are the test results of fresh catalyst activity evaluation of Examples 1-3 of the present invention;

[0040] Figure 4 are the test results for evaluating the activity of the aged catalysts of Examples 1-3 of the present invention;

[0041] Figure 5 are the test results of fresh catalyst activity evaluation of Examples 4-6 of the present invention;

[0042] Figure 6 These are the test results for evaluating the activity of the aged catalysts of Examples 4-6 of the present invention. DETAILED DESCRIPTION

[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0048] The present invention is configured as material 1 and material 2:

[0049] Optimizing the formation of active centers: The ratio of cerium, zirconium, and aluminum in the catalyst can be adjusted by adjusting the ratio of the two materials. A reasonable ratio of cerium, zirconium, and aluminum is conducive to the formation of active centers in the catalyst. Under different ratios, the materials will undergo different degrees of structural changes and interactions during pretreatment such as high temperature or actual reaction, prompting the active components to form specific active center structures on the carrier. The geometric shapes and electronic environments of these structures are more favorable for the adsorption and activation of reactant molecules and the conversion of reaction intermediates.

[0050] Controlling raw material costs: On the premise of meeting the requirements of natural gas catalytic performance, by adjusting the ratio of cerium, zirconium and aluminum and reasonably controlling the amount of cerium, zirconium and aluminum in the carrier, the preparation cost of the carrier and even the entire catalyst can be effectively reduced.

[0051] During the pulping process, the pulp contains precious metal active components, carriers, adhesives, reducing agents and other components. pH 2-7 helps maintain the colloidal stability of the pulp system. In this pH range, the interactions between the components are relatively balanced, and it is not easy to cause particle agglomeration and precipitation due to factors such as excessive or insufficient electrostatic repulsion and changes in solubility.

[0052] Good slurry stability can ensure that the slurry always remains in a uniform state during the subsequent stirring and sizing operations. After sizing, the slurry is not easy to fall off the honeycomb ceramic carrier, so that the active components and the carrier can continue to maintain a good dispersion and bonding relationship.

[0053] The ratio of cerium to zirconium in the composite material is certain. Cerium (Ce) has the ability to store oxygen. During the redox reaction, cerium can 3+ and Ce 4+ The oxygen storage capacity of cerium can be adjusted in time to supplement oxygen when the oxygen content fluctuates in the natural gas catalytic reaction, which is conducive to the efficient reaction. However, the oxygen storage capacity of cerium alone has certain limits. Under some more complex reaction conditions with large changes in oxygen demand, it may not be able to fully meet the requirements. After zirconium (Zr) is added, it can interact with cerium. Zirconium can change the crystal structure and surface properties of cerium, so that the oxygen storage performance of cerium is optimized.

[0054] Different cerium-zirconium ratios result in different cerium-zirconium solid solution structures and different oxygen storage properties. Within a certain range, as the zirconium content increases, the oxygen vacancy concentration of the solid solution will increase first and then stabilize. For example, at lower zirconium content, zirconium atoms gradually enter the cerium lattice to form more oxygen vacancies, making oxygen easier to adsorb, store and release, and enhancing oxygen storage performance; when the zirconium content is too high, the lattice may be excessively distorted or other phase structures may be formed, resulting in oxygen vacancies no longer increasing significantly or even decreasing, and the effect of improving oxygen storage performance becomes weaker.

[0055] Example 1

[0056] Step 1: Preparation of slurry:

[0057] (1) Take 3.3882g of palladium nitrate solution, 12.152g of material 1, 24.552g of material 2, 4.1043g of ascorbic acid, and 80mL of deionized water, add them to a beaker, immerse in a 60°C water bath, and stir until the weight reaches 87.23g

[0058] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0059] Step 2: Sizing and drying:

[0060] The slurry prepared in (2) was coated on a cordierite ceramic carrier so that the slurry loading amount was 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0061] Example 2

[0062] Step 1: Preparation of slurry: (1) Add 3.3882 g of palladium nitrate solution, 12.152 g of material 1, 24.552 g of material 2, 4.1984 g of glucose, and 80 mL of deionized water to a beaker and immerse in a 60°C water bath and stir until the weight reaches 87.23 g.

[0063] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0064] Step 2, slurry drying: the slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading amount is 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0065] Example 3

[0066] Step 1: Preparation of slurry: (1) Add 3.3882 g of palladium nitrate solution, 12.152 g of material 1, 24.552 g of material 2, 1.4464 g of ethylene glycol, and 80 mL of deionized water to a beaker and immerse in a 60°C water bath and stir until the weight reaches 87.23 g.

[0067] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0068] Step 2, slurry drying: the slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading amount is 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0069] Example 4

[0070] Step 1: Preparation of slurry: (1) Add 3.3882 g of palladium nitrate solution, 24.552 g of material 1, 12.152 g of material 2, 4.1043 g of ascorbic acid, and 80 mL of deionized water to a beaker, immerse in a 60°C water bath, and stir until the weight reaches 87.23 g.

[0071] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0072] Step 2: Slurry drying: The slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading amount is 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0073] Example 5

[0074] Step 1: Preparation of slurry: (1) Add 3.3882 g of palladium nitrate solution, 24.552 g of material 1, 12.152 g of material 2, 4.1984 g of glucose, and 80 mL of deionized water to a beaker and immerse in a 60°C water bath and stir until the weight reaches 87.23 g.

[0075] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0076] Step 2, slurry drying: the slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading amount is 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0077] Example 6

[0078] Step 1: Preparation of slurry: (1) Add 3.3882 g of palladium nitrate solution, 24.552 g of material 1, 12.152 g of material 2, 1.4464 g of ethylene glycol, and 80 mL of deionized water to a beaker and immerse in a 60°C water bath and stir until the weight reaches 87.23 g.

[0079] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0080] Step 2, slurry drying: the slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading amount is 120 g / L, dried for 4-6 hours, and then calcined at 500° C. for 2 hours to obtain a catalyst.

[0081] Comparative Example 1

[0082] (1) 1.6941 g of palladium nitrate solution, 12.152 g of material 1, and 11.423 g of deionized water were added to a beaker and stirred for 2 h. The mixture was evaporated to dryness in a 90°C water bath. The resulting powder was then calcined at 500°C for 2 h.

[0083] (2) Take 1.6941g of palladium nitrate solution, 24.552g of material 2, and 13.5036g of deionized water and prepare a powder according to step (1).

[0084] (3) Add the powder prepared in steps (1) and (2) into a ball mill, add 47.14 g of deionized water and 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, put it into the ball mill and stir rapidly.

[0085] Slurry drying: (4) The slurry prepared in (3) is coated on a cordierite ceramic carrier so that the slurry loading is 120 g / L, dried for 4-6 hours, and then calcined at 500°C for 2 hours to obtain a catalyst.

[0086] Comparative Example 2

[0087] Preparation of slurry: (1) Take 3.3882g of palladium nitrate solution, 12.152g of material 1, 24.552g of material 2, and 24.9266g of deionized water, add them into a beaker, soak and stir for 2h, then evaporate and dry in a 90℃ water bath, and then calcine the obtained powder at 500℃ for 2h

[0088] (2) Add the powder prepared in step (1) into a ball mill, add 47.14 g of deionized water and 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and put it into the ball mill and stir rapidly.

[0089] Slurry drying: (3) The slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading is 120 g / L, dried for 4-6 hours, and then calcined at 500°C for 2 hours to obtain a catalyst.

[0090] Comparative Example 3

[0091] (1) Take 3.3882g of palladium nitrate solution, 12.152g of material 1, 24.552g of material 2, 0.88g of NaBH4, and 80mL of deionized water and add them to a beaker, immerse in a 60°C water bath and stir until the weight reaches 87.23g

[0092] (2) Add the powder prepared in step (1) into a ball mill, add 4 g of acetic acid to adjust the pH of the slurry to 2-7, add 4 g of adhesive to keep the slurry viscous, and place it into a ball mill and stir rapidly.

[0093] Slurry drying: (3) The slurry prepared in (2) is coated on a cordierite ceramic carrier so that the slurry loading is 120 g / L. After drying for 4-6 hours, the slurry is calcined at 500° C. for 2 hours to obtain a catalyst.

[0094] The catalysts of Comparative Examples 1-3 were subjected to activity evaluation tests. The activity evaluation results are as follows: Figure 1 , 2 : The figures show the activity evaluation data of Comparative Examples 1 and 2 respectively

[0095] Table 1 Different comparative examples of catalyst CH 4 Activity data

[0096]

[0097] The catalysts of Examples 1-3 were subjected to activity evaluation tests. The activity evaluation results are as follows: Figure 3 , 4 : The figure shows the activity evaluation data of Example 1, Example 2 and Example 3 respectively

[0098] Table 2 Catalyst CH of different examples 4 Activity data

[0099]

[0100] From Tables 1 and 2, we can see that: from the data of Comparative Examples 1 and 2 and the Example, we can see that the catalyst performance of the reduction impregnation method is better than that of the traditional catalyst impregnation method under the same amount of precious metal. Example 3 using ethylene glycol reduction under the same evaluation conditions: fresh catalyst T 50 = 310℃ and using strong reducing agent NaBH 4 Comparative Example 3 Fresh Catalyst T Reduction 50 =429℃, which is a 119℃ drop in temperature, indicating that the catalytic performance is better when a reducing agent with milder reducing properties is used.

[0101] The catalysts of Examples 4-6 were subjected to activity evaluation tests. The activity evaluation results are as follows: Figure 5 , 6 : The figure shows the activity evaluation data of Example 4, Example 5 and Example 6 respectively

[0102] Table 3 Catalyst CH of different examples 4 Activity data

[0103]

[0104]

[0105] From Table 3, it can be seen that the comparison between Examples 4, 5, and 6 and Examples 1, 2, and 3 shows that the catalyst with a higher mass ratio of Material 1 has better catalytic performance after aging. The catalytic performance of Example 6 with ethylene glycol reduction Material 1: Material 2 = 2:1 after aging is better than that of Example 3 with Material 1: Material 2 = 1:2. 90 =356℃ and it can still maintain high catalytic activity. The higher proportion of material 1 may make the catalyst more resistant to aging.

[0106] The catalysts prepared in Examples 1-6 were in a fresh state. 50 The ignition temperature is significantly lower than that of the aged catalyst. 50It also maintains around 350°C, and the catalytic effect is better than traditional catalysts.

[0107] The catalytic effect of the catalyst on methane is the catalytic temperature T at which the catalyst converts 50% and 90% of methane. 50 、T 90 Measured by height, T 50 、T 90 The lower the value, the higher the conversion rate of methane can be achieved at a lower temperature, indicating that the catalyst activity is higher. The catalysts of Examples 1-6 using the reduction method in the present invention have a higher T value than those of Comparative Examples 1-2 prepared by the traditional method in the fresh aging state. 50 、T 90 A lower value indicates an improved catalytic performance for methane.

[0108] Finally, it should be noted that:

[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A catalyst for treating natural gas automobile exhaust, characterized in that: The catalyst is a precious metal Pd loaded on a mixed carrier of two composite materials, the composite material is composed of material 1 and material 2, the material 1 is a cerium-zirconium-aluminum composite material, wherein the cerium-zirconium-aluminum content ratio is Ce 0-20%, Zr 0-10%, Al 68-98%, and the content of other rare earth metals is 2%; the material 2 is a cerium-zirconium composite material, wherein the cerium-zirconium ratio is Ce 10-45%, Zr 35-45%, and the content of other rare earth metals is 0-20%.

2. The catalyst for treating natural gas automobile exhaust according to claim 1, characterized in that: The mass ratio of Pd in ​​material 1 and material 2 is 1:

1.

3. The catalyst for treating natural gas automobile exhaust according to claim 1, characterized in that: The mass ratio of material 1 to material 2 is 1:10~10:

1.

4. The method for preparing a catalyst for treating natural gas automobile exhaust according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Preparation of slurry (1) Mix palladium nitrate solution, material 1, material 2, reducing agent and deionized water in proportion, and immerse in a water bath at 60°C and stir; (2) adding the slurry prepared in step (1) into a ball mill and adding acetic acid to adjust the pH of the slurry to 2-7, adding a binder to keep the slurry viscous, and placing it into a ball mill and stirring rapidly; Step 2: Sizing and Drying The slurry prepared in (2) was coated on a cordierite ceramic carrier, dried for 2-4 h, and then calcined at 500° C. for 2 h to obtain a catalyst.

5. The method for preparing a catalyst for treating natural gas automobile exhaust according to claim 4, characterized in that: The reducing agent is one of ascorbic acid, glucose and ethylene glycol.

6. The method for preparing a catalyst for treating natural gas automobile exhaust according to claim 4, characterized in that: The content of the reducing agent is 5 times the amount of the precious metal Pd substance.

7. The method for preparing a catalyst for treating natural gas automobile exhaust according to claim 4, characterized in that: In the step 2, the coating amount of the slurry on the cordierite ceramic carrier is 120 g / L.

Citation Information

Patent Citations

  • High-stability coating material and preparation method of catalyst for purification of motor vehicle tail gas

    CN104941677A

  • Preparation method of low noble metal diesel vehicle oxidization catalyst and catalyst prepared by using same

    CN109225210A

  • Single-Pt three-way catalyst with high thermal stability and low noble metal loading capacity as well as preparation method and application of single-Pt three-way catalyst

    CN117718044A

  • Exhaust gas cleaning catalyst and manufacturing method therefor

    JP2005052805A

  • Method of producing catalyst support particles and a catalyzer using the catalyst support particles

    US20070281856A1